2018
DOI: 10.3390/s18124407
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Performance and Efficiency of Two Energy Transfer-Based Two-Photon Fluorescent Probes for pH

Abstract: The design and synthesis of fluorescent probes for monitoring pH values inside living cells have attracted great attention, due to the important role pH plays in many biological processes. In this study, the optical properties of two different two-photon fluorescent probes for pH are studied. The ratiometric sensing of the probes are theoretically illustrated. Meanwhile, the recognitional mechanisms of the probes are investigated, which shows the energy transfer process when react with H+. Specially, the calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…38 At present, the theoretical studies on TP-FRET probes are still very limited. [41][42][43][44][45][46] Wang et al designed a TP-FRET ratiometric fluorescent probe, for which a rhodamine spirolactam and a naphthalene derivative were selected as the energy acceptor and donor respectively. 41 The FRET and the fluorescence OFF-ON effects are fully rationalized by quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 At present, the theoretical studies on TP-FRET probes are still very limited. [41][42][43][44][45][46] Wang et al designed a TP-FRET ratiometric fluorescent probe, for which a rhodamine spirolactam and a naphthalene derivative were selected as the energy acceptor and donor respectively. 41 The FRET and the fluorescence OFF-ON effects are fully rationalized by quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and coworkers theoretically investigated the optical properties and recognition mechanism of a series of TP fluorescent probes. [42][43][44] The influence of the donor and linker on the sensing performances was demonstrated. These theoretical studies revealed the microscopic FRET mechanism behind the experimental observations and provided useful structure and property relationship for the design of TP-FRET fluorescent probes.…”
Section: Introductionmentioning
confidence: 99%